Loss of MHC-I antigen presentation correlated with immune checkpoint blockade tolerance in MAPK inhibitor-resistant melanoma - Yu, Jing; Wu, Xi; Song, Jinen; Zhao, Yujie; Li, Huifang; Luo, Min; Liu, Xiaowei (Frontiers in Pharmacology, 2022)
Immune checkpoint blockade and MAPK-targeted combined therapy is a promising regimen for advanced melanoma patients. However, the clinical benefit from this combo regimen remains limited, especially in patients who acquired resistance to MAPK-targeted therapy. Here, we systematically characterized the immune landscape during MAPK-targeted therapy in patients and mouse melanoma models. We observed that both the abundance of tumor-infiltrated T cells and the expression of immune-related genes were up-regulated in the drug-responsive period, but down-regulated in the resistance period, implying that acquired drug resistance dampens the antitumor immune response. Further transcriptomic dissection indicated that loss of MHC-I antigen presentation on tumor cells plays a critical role in the reduction of T cell infiltration during drug resistance. Survival analysis demonstrates that loss of antigen presentation and reduction of T-cell infiltration during acquired drug resistance are associated with poorer clinical response and prognosis of anti-PD-1 therapy in melanoma patients. In addition, we identified that alterations in the MAPK inhibitor resistance-related oncogenic signaling pathway closely correlated with deficiency of MHC-I antigen presentation, including activation of the PI3K-mTOR, MAPK, and Wnt pathways. In conclusion, our research illuminates that decreased infiltration of T cells is associated with acquired drug resistance during MAPK-targeted therapy, which may underlie the cross-resistance to immune checkpoint blockade.